2015
DOI: 10.1080/23279095.2015.1048514
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality and neuropsychological assessment: The reliability of a virtual kitchen to assess daily-life activities in victims of traumatic brain injury

Abstract: Traumatic brain injury (TBI) causes impairments affecting instrumental activities of daily living (IADL). However, few studies have considered virtual reality as an ecologically valid tool for the assessment of IADL in patients who have sustained a TBI. The main objective of the present study was to examine the use of the Nonimmersive Virtual Coffee Task (NI-VCT) for IADL assessment in patients with TBI. We analyzed the performance of 19 adults suffering from TBI and 19 healthy controls (HCs) in the real and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 48 publications
0
32
0
1
Order By: Relevance
“…Allain et al [12] benchmarked a VR task against a closely corresponding real-world task and found that a VR paradigm could be a more complex yet ecologically valid measure. As for the reasons for the complexity of the VR, a recent study [31] proposed that VR interface with a mouse and keyboard is unnatural to use. Thus, different mental schemes would be associated in VR and real tasks, and consequently more attention will be paid to do VR tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allain et al [12] benchmarked a VR task against a closely corresponding real-world task and found that a VR paradigm could be a more complex yet ecologically valid measure. As for the reasons for the complexity of the VR, a recent study [31] proposed that VR interface with a mouse and keyboard is unnatural to use. Thus, different mental schemes would be associated in VR and real tasks, and consequently more attention will be paid to do VR tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, different mental schemes would be associated in VR and real tasks, and consequently more attention will be paid to do VR tasks. Note that previous VR contents [12,13,31] were mostly based on non-immersive VR environment with a mouse and keyboard. As mentioned, the VDLT proposed in this study is an immersive VR-based test that subjects can conduct virtual IADL tasks with their own body (i.e., hand and head).…”
Section: Discussionmentioning
confidence: 99%
“…Our task presents similarities in scope and design with the Nonimmersive Virtual Coffee Task (NI-VCT), which was developed in a 3D VR system and was recently published by Besnard et al [84]. However, two main differences could impact the generalization of the selected technology to the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…For example, only a handful of studies have established the ecological and construct validity of simulated environments [84]. VR might produce motion sickness (discomfort, nausea, vomiting, headache, fatigue, etc.)…”
Section: Neuropsychological Assessment In Simulated Environmentsmentioning
confidence: 99%
“…In addition, using non-immersive systems, other studies included virtual tasks such as preparing coffee with an electric coffee maker [64,65]. They were developed to evaluate performance in IADLs, analyzing errors and validating them for populations with traumatic brain injury [65] and Alzheimer's disease [64]. Other virtual tasks related to community mobility were also developed, such as taking a bus [66].…”
Section: Types Of Instruments According To the Methodology Usedmentioning
confidence: 99%